2016
DOI: 10.1111/jpi.12317
|View full text |Cite
|
Sign up to set email alerts
|

Low melatonin production by suppression of either serotonin N‐acetyltransferase or N‐acetylserotonin methyltransferase in rice causes seedling growth retardation with yield penalty, abiotic stress susceptibility, and enhanced coleoptile growth under anoxic conditions

Abstract: Serotonin N-acetyltransferase (SNAT) and N-acetylserotonin methyltransferase (ASMT) are the last two key enzymes for melatonin biosynthesis in living organisms. In this study, we demonstrated that transgenic rice (Oryza sativa L.) plants, in which expression of either endogenous SNAT or ASMT was suppressed, had reduced melatonin synthesis, confirming that both SNAT and ASMT are functionally involved in melatonin synthesis. The melatonin-deficient SNAT rice had retarded seedling growth, which was partially rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 61 publications
7
93
0
Order By: Relevance
“…In this report, we observed a novel phenotype in melatonin‐deficient transgenic rice plants in which SNAT2 gene expression was suppressed . This phenotype was not previously identified in transgenic rice plants with suppressed SNAT1 expression . The SNAT2 RNAi lines exhibited a dwarf phenotype with erect leaves reminiscent of BR‐deficient phenotype, indicating that melatonin takes part in determining BR levels in plants.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this report, we observed a novel phenotype in melatonin‐deficient transgenic rice plants in which SNAT2 gene expression was suppressed . This phenotype was not previously identified in transgenic rice plants with suppressed SNAT1 expression . The SNAT2 RNAi lines exhibited a dwarf phenotype with erect leaves reminiscent of BR‐deficient phenotype, indicating that melatonin takes part in determining BR levels in plants.…”
Section: Introductionmentioning
confidence: 57%
“…However, the auxinic effect and induction of auxin by melatonin in plants are controversial, suggesting the involvement of other plant hormones. The growth effect of melatonin in plants was indicated in melatonin‐deficient plants resulting from an Arabidopsis SNAT1 knockout mutant or from transgenic downregulation of the SNAT1 gene in rice . These plants were smaller than their counterpart wild types, indicating that melatonin is associated with plant growth, albeit the actual mode of melatonin action is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, melatonin biosynthetic genes, such as TDC and T5H , may not be appropriate genetic tools to modulate melatonin levels in plants via genetic modification by overexpression and RNAi suppression techniques. Therefore, SNAT and ASMT genes, which are involved in the last two steps of melatonin biosynthesis, have been frequently utilized to regulate melatonin levels in plants . Unfortunately, no plant SNAT ‐overexpressing transgenic plants have been reported to date, although SNAT plays a regulatory role in plant melatonin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was cleared by centrifugation at 12 000× g for 15 minutes, boiled at 95°C for 25 minutes, and placed on ice for 5 minutes. MDA content was recorded at wavelengths of 440, 532, and 600 nm using a spectrophotometer (Optizen Pop‐Bio) as described previously . MDA was quantified using a molar extinction coefficient of 156 per nmol L −1 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…In vivo studies have also found a role for serotonin in shoot growth. In transgenic rice (Oryza sativa L.) that lack the downstream enzyme serotonin N-acetyltransferase (SNAT), which is involved in the conversion of serotonin to melatonin, serotonin content was increased and was associated with increased coleoptile growth but slower overall seedling growth [37] . In comparison, an earlier study by Kang et al (2007) found that overexpression of TDC, which despite increasing serotonin levels by up to 25 fold, showed no difference in growth.…”
Section: Vegetative Growth and Morphogenesismentioning
confidence: 99%